O Brasil descortinado por Caio Prado Jr.: gênese e reiteração do círculo vicioso - Souza, Ângela Maria (2009)
This work intends to clarify the analysis developed by the marxist, militant and intellectual Caio Prado Júnior (1907-1990) about the Brazilian history, from colony to 1960s, based on the vicious circle, in its historical specificities, over which the Brazilian sociability was built and restored. It is the necessary enlargement of the study developed in the master´s dissertation (The Brazil of Caio Prado Jr. in the Revista Brasiliense 1955-64, presented in 2004), since although considered classic, the historian from São Paulo is known very little by his own texts. Besides that, his huge intelectual works about the Brazilian reality can offer vast elements of research not yet exhausted. To elaborate this study it was adopted as analitical parameter the imanent analysis of his works, which implies the apprehension of the central nexes which support the author´s thinking, trying to respect the nature itself of his production, that is, the way he conceived and expressed it. In the investigation of his works about Brazil, it was verified a remarkable aspect in all of them: the reiteration of the vicious circle commonly denounced, that is, it was an exogenous economy considered as a priority to the detriment of the domestic interests. Product of the colonial statute in its origin and which became crystallized along the years, configurating an unequal and subordinate growth, which endangered a self-sustained development and also obstructed the country´s transition from a colonial economy to a national economy. Vicious circle which along history, was made of several elements and circumstances but which kept its essencial basis, the exclusion of the working classes from the results of the wealth produced and from the political processes, the hard living conditions of popular classes and the usual violence unleashed against them. It makes clear the presence of the unlucky past in our present which, launched during the colony, it was not defeated in the process of independence and was reaffirmed during the republic